A Embrapa na reprodução do capital no campo - Cardoso, Victor de Souza (2022)
From its creation till its contemporaneity, Embrapa perpetuates itself as a prop of the capital expansion in the Brazilian countryside, articulating and enabling the scientifictechnological means necessary not only to guarantee the high levels of productivity but also to assure the ideal conditions of the agricultural production. For this, the public enterprise changed its strategies incorporating concepts and practices in its repertory as emerged new political-economical demands over time. Such transformations did not mean a modification of its principal goal, that is: the aggregation of competitiveness of the Brazilian agribusiness - even though, in the latest years, in the light of the signs as rural development, social inclusion, and environmental sustainability. In this scenery, the present research aimed to analyze the production of science and technology in the capital's reproduction in Sergipe's countryside through the Embrapa Tabuleiros Costeiros (CPATC). For this, the study was grounded on the theoretical-methodological assumptions of historical-dialectical materialism, operating them through two methodological instruments: bibliographic research and documentary research. Therefore, the realized research permit asserting the centrality of Embrapa as a controller, supervisory, and organizer instrument of the public national agricultural research, which, jointly with the rural credit and extension, permit the continuity of the capitalistic accumulation in the countryside. In Sergipe, the CPATC's actions are directed especially – but not only – at some cultivars such as sugarcane, citrus, corn, and, recently, soybean – this last one through the construction of a new agricultural frontier to Nordeste intended for the soybean culture and composed of part of the state's cities of Sergipe, Alagoas, and Bahia, the SEALBA. On the other hand, in harmony with the general guidelines of the enterprise for social inclusion of the considered "not adjusted" to the capital logic, the referent research center started to act in the construction of the ecological based alternatives forms of production as instruments for the small peasant producer's market insertion.